The Comfort Zone. - Grier, David Alan (Computer (00189162), 2013)
Interdisciplinary work is a key part of computing, but it often demands that we drop old conceptions and learn to think as others do. The Web extra at http://youtu.be/y8BSzeoZDCA is a video segment in which author David Alan Grier expands on his Errant Hashtag column, in which he discusses how interdisciplinary work is a key part of computing, but that it often demands we drop old conceptions and learn to think as others do.